Media disinformation in Peru: systematic review of university theses - Turpo-Gebera , Osbaldo; Quispe-Mamani, Edgar; Contreras-Mejía , Ofelia; Contreras-Mejia , Monica (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Understanding the evolution and implications of media disinformation in Peru is crucial, as it requires a systematic review of university theses. This study reveals the growing interest that has been generated around disinformation as an object of study, although its distribution is not uniform in disciplinary and geographical terms. Theses address a variety of topics that reflect the diversity and importance of disinformation. Various forms of disinformation manifestation and propagation are analyzed, and recommendations are proposed to counteract it.